European Multilingualism : Current Perspectives and Challenges. - Rindler Schjerve, Rosita (Channel View Publications, 2012)
This book provides a broad sociolinguistic perspective on major questions of political and cultural Europeanization. It is concerned with European multilingualism as it actually results from the intersecting endeavour of policy making and scientific research. This volume argues that the EU must overcome the major discrepancies of its linguistic diversity politics by developing into a multiple inclusive society beyond the nation-state in order to seriously unfold European multilingualism as a political goal. Expanding on the theoretical and methodological approaches developed within the EU proj.